Frequent users of emergency services: associated factors and reasons for seeking care - Aline Marques Acosta; Maria Alice Dias da Silva Lima (Universidade de São Paulo, 2015)
Aim: to identify the profile of frequent users of emergency services, to verify the associated factors and to analyze the reasons for the frequent use of the services. METHOD: An explanatory sequential type mixed method was adopted. Quantitative data were collected from the electronic medical records, with a sample of 385 users attended four or more times in an emergency service, during the year 2011. Qualitative data were collected through semi-structured interviews with 18 users, intentionally selected from the results of the quantitative stage. Quantitative data were analyzed using descriptive and inferential statistics and qualitative data using thematic analysis. RESULTS: It was found that 42.9% were elderly, 84.9% had chronic diseases, 63.5% were classified as urgent, 42.1% stayed for more than 24 hours in the service and 46.5% were discharged. Scheduled follow-up appointment, risk classification, length of stay and outcome were factors associated with frequent use. The reasons for seeking the services were mainly related to the exacerbation of chronic diseases, to easier access and concentration of technology, to the bond, and to the scheduled appointments. CONCLUSIONS: The results contribute to comprehending the repeated use of emergency services and provide additional data to plan alternatives to reduce frequent use.